2022
DOI: 10.1002/aic.17926
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐by‐control of intensified continuous filtration‐drying of active pharmaceutical ingredients

Abstract: Continuous manufacturing and closed‐loop quality control are emerging technologies that are pivotal for next‐generation pharmaceutical modernization. We develop a process control framework for a continuous carousel for integrated filtration‐drying of crystallization slurries. The proposed control system includes model‐based monitoring and control routines, such as state estimation and real‐time optimization, implemented in a hierarchical, three‐layer quality‐by‐control (QbC) framework. We implement the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Quality control in pharmaceutical drying is an essential aspect of the manufacturing process, and it involves various measures to ensure the final product's quality, safety, and efficacy. Here are some of the quality control measures in detail [39,40].…”
Section: Quality Control In Pharmaceutical Dryingmentioning
confidence: 99%
“…Quality control in pharmaceutical drying is an essential aspect of the manufacturing process, and it involves various measures to ensure the final product's quality, safety, and efficacy. Here are some of the quality control measures in detail [39,40].…”
Section: Quality Control In Pharmaceutical Dryingmentioning
confidence: 99%
“…The operation behavior was characterized by Acevedo et al and Ottoboni et al [7,33]. Further studies demonstrated the capabilities for product isolation [42,43], integration of continuous crystallization equipment [44][45][46], modeling [44,47], and most recently digital design and simulation [47][48][49]. Due to the quasicontinuous operation, the residence times on each of the positions are coupled and the RT is set by the time spent on each position.…”
Section: Continuous Filter and Dryermentioning
confidence: 99%
“…Filtration is typically performed in order to gain solid isolation from the product. The evaluation of filtration performance is frequently determined by the recoverable mass (cake yield), the solvent retention of the filter cake, the filterability and purity of the crystals. , Continuous integrated filtering is an emerging field of research in the pharmaceutical sector in both mathematical modeling and experimentation. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Process intensification is achieved by a holistic application of (i) continuous manufacturing, (ii) process integration, (iii) intensified unit operation using oscillatory mixing, (iv) intensified process based on spherical agglomeration, (v) novel equipment design with automation, and (vi) application of integrated array of process analytical technology (PAT) tools. We have previously investigated various components of this overall process, such as continuous manufacturing, , utilizing novel equipment, ,, use of process analytical technology (PAT) tools in monitoring processes, , feedback controls and quality by control (QbC) methods, , digital models via model-based optimizations, ,,,,, and combination of various mechanism ,,,,, (i.e., spherical agglomeration, milling, nucleation in porous media). PAT tools in conjunction with mathematical models have been used successfully for the mechanistic understanding of spherical crystallization and agglomeration. ,, Peña and Nagy (2015) were the first to report the continuous integration of crystallization and spherical agglomeration in a coupled two-stage stirred tank system.…”
Section: Introductionmentioning
confidence: 99%